2013
DOI: 10.3382/ps.2012-02992
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plastic slatted floors compared with pine shaving litter on Pekin Duck condition during the summer months

Abstract: The management and well-being of commercial Pekin ducks has been studied in the European Union where straw is the predominant litter source. In the United States, however, the most prevalent litter is wood shavings, with a recent trend toward using plastic slatted flooring. A previous study in the United States evaluated the relationship between flooring type (litter, slats) and duck condition during winter months and found very few differences between the 2 in terms of overall duck condition. The purpose of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 14 publications
3
36
2
Order By: Relevance
“…The biological conditions of the ducks were assessed through body condition scoring, analyses of gut microbial ecology, and serum hormone levels for corticosterone ( CS ) and angiotensin II ( AgII ). Body condition scoring was performed at ages 9, 23, and 33 d using a published rubric (Fraley et al, 2013 ; Karcher et al, 2013 ; Colton and Fraley, 2014 ). At the 3 specified ages, researchers used gates to randomly select 25 ducks in four corners of each pen, resulting in a total of 100 ducks/pen.…”
Section: Methodsmentioning
confidence: 99%
“…The biological conditions of the ducks were assessed through body condition scoring, analyses of gut microbial ecology, and serum hormone levels for corticosterone ( CS ) and angiotensin II ( AgII ). Body condition scoring was performed at ages 9, 23, and 33 d using a published rubric (Fraley et al, 2013 ; Karcher et al, 2013 ; Colton and Fraley, 2014 ). At the 3 specified ages, researchers used gates to randomly select 25 ducks in four corners of each pen, resulting in a total of 100 ducks/pen.…”
Section: Methodsmentioning
confidence: 99%
“…Based on higher levels of nal BW, average daily gain (ADG), average daily feed intake (ADFI) and lower feed conversion rate (FCR) in NRS ducks, Zhang et al [9] concluded Chaohu ducks had better growth performance in NRS than in FRS. By comparing plastic oor net-rearing and litter oor-rearing, Pekin ducks were also found higher ADG in NRS [10]. However, study on Cherry Valley ducks reported higher ADG and lower FCR in FRS, and concluded FRS was one of the best duck rearing systems compared with NRS [12].…”
Section: Introductionmentioning
confidence: 90%
“…Both of them can create better hygiene than other rearing systems as ducks have less contact with their excreta [2,9]. Floor-type had either positive or negative correlations with the environment and physiological characteristics of ducks during rearing [10]. Previous studies on this variable indicated multifaceted effects on ducks.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, a major concern for today's poultry industry is high levels of ammonia (NH 3 ) and N loss from reusing litter that can have a negative effect on poultry production and litter quality (Proch et al, 2019). Consequently, the reuse of litter could directly and indirectly affect poultry production and welfare parameters (foot pad lesions, lameness and eye and nostril health) (Hess et al, 2009;Fraley et al, 2013). Several studies have investigated different litter additives to control NH 3 emission and N loss from poultry litter to improve poultry production (Moore et al, 2000;Moore and Edwards, 2007).…”
Section: Introductionmentioning
confidence: 99%